Improvement of electrical, thermal, and mechanical properties of poly(methyl methacrylate)/poly(ethylene oxide) blend using graphene nanosheets. (September 2019) - Aram, Elham; Ehsani, Morteza; Khonakdar, Hossein Ali; Abdollahi, Serveh
Poly(methyl methacrylate) (PMMA)/poly(ethylene oxide) (PEO) (90/10) nanocomposites containing various amounts of graphene nanoplatelets were fabricated by solution method and then the effects of graphene concentration on morphology, thermal, mechanical, and electrical properties of the nanocomposites were investigated. Characterization by electron microscopy and X-ray diffraction of the nanocomposites showed a relatively good dispersion of graphene sheets in the polymer matrix. The results indicated that thermal stability, glass transition temperature, and mechanical properties of PMME/PEO blend improved by increasing graphene concentration. The electrical properties of polymer nanocomposites revealed a significant improvement with increasing the amount of graphene and the percolation threshold was about 3.33 wt% of graphene.